Constant savings rates and quasi-arithmetic population growth under exhaustible resource constraints - Geir B. Asheim; Wolfgang Buchholz; John M. Hartwick; Tapan Mitra; Cees A. Withagen (Center for Economic Studies and ifo Institute (CESifo), 2005)
In the Dasgupta-Heal-Solow-Stiglitz model of capital accumulation and resource depletion we show the following equivalence: If an efficient path has constant (gross and net of population growth) savings rates, then population growth must be quasi-arithmetic and the path is a maximin or a classical utilitarian optimum. Conversely, if a path is optimal according to maximin or classical utilitarianism (with constant elasticity of marginal utility) under quasiarithmetic population growth, then the (gross and net of population growth) savings rates converge asymptotically to constants.
Keywords: Q10; Q32; 330; constant savings rate; quasi-arithmetic population growth; Sparquote; Bevölkerungswachstum; Kapitalbilanz; Natürliche Ressourcen; Wachstumstheorie